Electrolyte Imbalance in Admitted Diabetic Patients: Patterns and Factors Responsible- A Cross Sectional Study (KYAMC Journal, 2017)
Diabetes Mellitus (DM) is a major burden upon health-care facilities in all countries. Electrolyte imbalances (EI) are very common in admitted patients with diabetes which leads to substantial morbidity and mortality. Every patient with diabetes needs thorough evaluation for the etiology and precipitating factors responsible for EI and therefore rational management. Data regarding the incidence of EI in DM in our country is limited. There is no existing record for profiling of EI in Bangladeshi diabetic subjects. The objective of this study was to find out the common types of EI in hospitalized diabetic patients and to determine the influencing factors responsible for them. Samples were selected from all adult nonpregnant diabetic patients admitted in the indoor, department of Medicine with electrolyte disturbances irrespective of their cause of admission. A total number of 150 admitted diabetic patients with electrolyte imbalance were interviewed, examined physically and laboratory specimen taken for biochemical analysis. Information was collected in a semi structured data collection form for analysis. Hyponatremia was found to be the most common EI in admitted diabetic patients. Electrolyte imbalance was found to be more common in the aged and female populations. Common factors influencing EI were vomiting, diarrhea, sweating, uncontrolled diabetes with severe hyperglycemia and certain drugs especially diuretics. Among the other well established complications of diabetes like acute metabolic complications, microangiopathy and macroangiopathy, EI should also be considered especially in the admitted patients.KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 458-466